Good time cowboy - Yates, Maisey (Yates, Maisey. Gold Valley, 2018)
When Lindy Parker lost her cheating husband, she gained a vineyard. She'll do anything for Grassroots Winery, including teaming up with the hottest devil she knows, rancher Wyatt Dodge. Wyatt is her ex's friend and has an ego as big as the bulls he rides. But in spite of that, disciplined Lindy has always wanted him. Lightning struck Wyatt Dodge the first time he saw Lindy Parker. But there were two problems with that: she was married to his friend, and Wyatt doesn't do strings. But now Lindy is free, and the two of them can finally explore the heat that's burned between them for so long. But can Lindy make this good time cowboy decide on forever?